Whole-Brain Network Connectivity Underlying the Human Speech Articulation as Emerged Integrating Direct Electric Stimulation, Resting State fMRI and Tractography - Zacà, Domenico; Corsini, Francesco; Rozzanigo, Umberto; Dallabona, Monica; Avesani, Paolo; Annicchiarico, Luciano; Zigiotto, Luca; Faraca, Giovanna; Chioffi, Franco; Jovicich, Jorge; Sarubbo, Silvio (Frontiers in Human Neuroscience, 2018)
Production of fluent speech in humans is based on a precise and coordinated articulation of sounds. A speech articulation network (SAN) has been observed in multiple brain studies typically using either neuroimaging or direct electrical stimulation (DES), thus giving limited knowledge about the whole brain structural and functional organization of this network. In this study 7 right-handed patients underwent awake surgery resection of low-grade gliomas (4) and cavernous angiomas. We combined pre-surgical resting state fMRI and diffusion MRI together with speech arrest sites obtained intra-operatively with DES to address the following goals: i) determine the cortical areas contributing to the intrinsic functional SAN using the speech arrest sites as functional seeds for resting state fMRI; ii) evaluate the relative contribution of gray matter terminations from the two major language dorsal stream bundles, the superior longitudinal fasciculus (SLF III) and the arcuate fasciculus (AF) and iii) evaluate the possible pre-surgical prediction of SAN with resting state fMRI. In all these right-handed patients the intrinsic functional SAN included frontal, inferior parietal, temporal and insular regions symmetrically and bilaterally distributed across the two hemispheres regardless of the side (4 right) of speech arrest evocation. The SLF III provided a much higher density of terminations in the cortical regions of SAN in respect to AF. Pre-surgical rs-fMRI data demonstrated moderate ability to predict the SAN. The set of functional and structural data provided in this multimodal study characterized, at a whole-brain level, a distributed and bi-hemispherical network subserving speech articulation.